2013
DOI: 10.1186/1756-8935-6-8
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate GAGA factor associated insulator elements demarcate homeotic genes in the HOX clusters

Abstract: BackgroundHox genes impart segment identity to body structures along the anterior-posterior axis and are crucial for the proper development of all organisms. Multiple regulatory elements, best defined in Drosophila melanogaster, ensure that Hox expression patterns follow the spatial and temporal colinearity reflected in their tight genomic organization. However, the precise mechanisms that regulate colinear patterns of Hox gene expression remain unclear, especially in higher vertebrates where it is not fully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…This is noteworthy given our findings that EOR-1 is found in less accessible and potentially even nucleosome-occupied regions of the genome and that the EOR-1 motif is predictive of increased accessibility in development. GAGA-factors are conserved regulators of gene expression (Ohtsuki and Levine 1998;Mahmoudi et al 2002;Petrascheck et al 2005;Srivastava et al 2013), and a GAGA motif has been found to be necessary for enhancer functionality in C. elegans (Harfe et al 1998). Indeed, two out of five of the novel validated enhancers identified in this study (nhr-25 and swip-10) contain an EOR-1/GAGA motif.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is noteworthy given our findings that EOR-1 is found in less accessible and potentially even nucleosome-occupied regions of the genome and that the EOR-1 motif is predictive of increased accessibility in development. GAGA-factors are conserved regulators of gene expression (Ohtsuki and Levine 1998;Mahmoudi et al 2002;Petrascheck et al 2005;Srivastava et al 2013), and a GAGA motif has been found to be necessary for enhancer functionality in C. elegans (Harfe et al 1998). Indeed, two out of five of the novel validated enhancers identified in this study (nhr-25 and swip-10) contain an EOR-1/GAGA motif.…”
Section: Discussionmentioning
confidence: 95%
“…This GAGA/EOR-1 motif was also present in two of the five functional enhancers that we experimentally validated, including the nhr-25-associated enhancer described above. TFs binding GAGA motifs have been identified as modulators of chromatin structure dynamics from plants to humans (Lund et al 2013;Srivastava et al 2013;Hecker et al 2015), and the GAGA motif itself is required for full functionality in two previously defined C.…”
Section: Specific Motifs For Transcription Factors Predict Changes Inmentioning
confidence: 99%
“…Interspersed between the peaks of histone H3 enrichment, we observed a distinctive pattern of gaps, which we defined as histone free regions or HFRs (Srivastava et al, 2013). Using a bioinformatics approach to map the extent and location of the HFRs (Srivastava et al, 2014), we showed that the gaps in H3 binding mapped precisely to the intergenic regions separating adjacent Hox genes.…”
Section: Boundary Activity At the Vertebrate Hox Clusters: A Role Formentioning
confidence: 95%
“…A boundary element characterized at the mouse Hoxd locus between the Evx2 and (Srivastava et al, 2013) showing unenriched HFR regions (black arrows) interspersed with histone H3 peaks. Y-axis shows the normalized log ratio (NLR) values for all probes tiled along the cluster (X-axis) with the position of the Hoxd genes marked as boxes below the graph (transcriptional orientation is indicated).…”
Section: Boundary Activity At the Vertebrate Hox Clusters: A Role Formentioning
confidence: 99%
See 1 more Smart Citation